Uso de drogas no ensino superior : um estudo longitudinal de 8 anos - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
Drug consumption is a serious public health problem, especially in the studentpopulation, considering its potential for dependence and the variousassociated damages. This study aimed to analyze the predictive factors ofdrug consumption by university students. This is a longitudinal study, with datacollection in the years 2014, 2015, 2019, and 2022 carried out with 1.020students. For data collection, a self-administered questionnaire was used,based on the World Health Organization Guidelines for Research onSubstance Use among Students, validated for the Brazilian reality, composedof 30 questions related to socioeconomic and academic issues and the use ofdrugs. The analysis was performed using the SPSS statistical software. Theassociation between drug use and independent variables was evaluated usingthe Chi-square test, Fisher's Exact Test, and Ordinal Logistic Regression. Thestudy complied with the ethical precepts of Resolution n. 466/2012 of theConselho Nacional de Saúde. The mean prevalence of use of alcohol,tobacco, marijuana, solvents and inhalants, hallucinogens, and cocaine was75.9%, 17.7%, 23.3%, 11.6%, 10.2%, and 4.5%, respectively. The averageprevalence of psychotropic medication use, namely tranquilizers,amphetamines, opiate analgesics, anabolic steroids, anticholinergics, andcodeine-based syrups was 15.1%, 10.1%, 2.5%, 1.9%, 1.2%, and 0.7%,respectively. The variables that best predicted alcohol use were: course,sports practice, tobacco use, amphetamines, solvents and inhalants, andopiate analgesics. As for the predictor model of tobacco use, the variables thatshowed the greatest adjustment in the ordinal logistic regression were: type ofcourse, use of anxiolytics and barbiturates, marijuana, cocaine, solvents andinhalants, and anabolic steroids. For the predictor model of the use oftranquilizers, the variables that showed the greatest adjustment were: sex,marital status, type of course, where he lived most of his life, consumption oftobacco, amphetamines, and opiate analgesics. Regarding the predictormodel for marijuana use, the variables that showed the greatest fit to the modelwere: marital status, type of course, if you work, have a religion, use of alcohol,tobacco, tranquilizers, cocaine, solvents and inhalants, and hallucinogens.
Keywords: Drogas lícitas; Drogas ilícitas; Psicotrópicos; Estudantes - Educação superior; Legal drugs; illicit drugs; Psychotropics; Students - College education; CIENCIAS DA SAUDE::FARMACIA